Adjusting comprehensive properties of biodegradable Zn-Mn alloy through solution heat-treatment. (June 2020) - Sun, Jiang; Zhang, Xin; Shi, Zhang-Zhi; Gao, Xi-Xian; Liu, Xue-Feng; Wang, Jian-Quan; Wang, Lu-Ning
Highlights: Solution heat-treatment adjusts properties of Zn-Mn alloy for the first time. A solid solution hardening effect of 17 HV in maximum is achieved. Corrosion resistance is much enhanced. L929 cell viability is elevated to about 100% after MnZn13 dissolution. Abstract: Adjusting comprehensive properties is a common concern in the community of biodegradable metals. The present work reveals that a simple solution heat-treatment can achieve this goal in Zn-0.8Mn alloy. Solid dissolution of MnZn13 into Zn matrix hardens the alloy, enhances its corrosion resistance in Hanks' solution, and significantly promotes L929 cell viability. Meanwhile, good rBMSCs viability and antibacterial ability of E. coli of the alloy are maintained, insensitive to the heat-treatment.